SYNTACTIC AND SEMANTIC FEATURES OF IDIOMS DENOTING HEALTH IN ENGLISH AND VIETNAMESE / Kieu Thu Hien; NHDKH Dr Mai Thi Loan - Kieu, Thu Hien
One of the most effective and colorful ways to transfer culture is the use of idioms which, however cause several troubles for English learners because of their confusing meanings. To help learners have a better understanding of idioms, particularly idioms denoting health, this thesis conducts a study of syntactic and semantic features of idioms denoting health in English and Vietnamese. Basing on the description and analysis of distinguishing features, the similarities and differences of idioms in the two languages are presented. In addition, both the descriptive and contrastive methods are used in combination with the qualitative and quantitative approach. The investigation is based on 109 samples of English idioms and 109 Vietnamese idioms denoting health from a wide variety of dictionaries and books about idioms. These findings also aim at offering some practical implications for teaching and learning English.